HAZEL GRACE LANCASTER’S STRUGGLES TO CREATE HER ESSENCE IN JOHN GREEN’S THE FAULT IN OUR STARS - ARIATI, DINAR UTAMI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: existentialism, concept of death, The Fault in Our Stars Existentialism is a way people try to create the meaning of life. The Fault in Our Stars novel tells how Hazel Grace Lancaster tries to create her essence in her last stage of cancer. This study is conducted to analyze how Hazel Grace Lancaster struggles to create her essence as portrays in John Green’s novel The Fault in Our Stars.The writer proposes qualitative approach to describe every step which is taken by Hazel to create her essence. Existentialism approach is used to make the writer focus to answer the problem of the study. The writer also uses concept of death by Martin Heidegger to get deeper understanding of Hazel’s struggles.This study reveals that Hazel passes three stages to create her essence. First, she sees her death as a threat for the life of others. Second, she starts appreciate life regarding the consciousness that death has its positive sides and confronts with death makes Hazel realize that live is hard to achieve. Hazel also confronts with her boyfriend’s death which happens unexpectedly. That problem makes Hazel reach her final stage that she knows her life will continue even though the people whom she loves already died.For the conclusion, Hazel proves that to create her essence, she lives andstands as an individual with accepting the fact that cancer is part of her life andaccepting death as the key of life. The following researchers are suggested toanalyze Hazel Grace Lancaster’s complexities by using psychological approach.